(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
This article proposes an alternative didactic methodology to determine the density of a liquid using the relationship between the mass of a body and its submerged height. An experiment is performed by placing a floating wooden cube in a transparent fish tank with water. Copper coins of equal mass are added to increase the total mass of the body, and the submerged height is measured with a tape measure. Although no direct proportionality was found between mass and submerged height according to the theoretical model, a linear relationship was observed, influenced mainly by the absorption of water in the wooden cube.